Scheduling jobs on multi-processors - Neetika, Bansal (2012)
A wide variety of research has been done to study the NP-complete optimization problem of multi-processor scheduling. In today’s world, where energy efficiency is gaining importance, the scheduling algorithms need to optimize both performance and energy consumption. This report focuses on scheduling of multiple job sets, using a three-level framework and dynamic speed scaling, with the objective of minimizing the bi-criterion metric of total response time plus energy.